The MRI-based vertebral bone quality score is a predictor of pedicle screw loosening following instrumented posterior lumbar fusion - Yung-Hsueh Hu; Jian-Hong Chou; Yu-Cheng Yeh; Ming-Kai Hsieh; Tsung-Ting Tsai; Wen-Jer Chen; Lih-Hui Chen; Po-Liang Lai; Chi-Chien Niu (Scientific Reports)
Abstract Objective: To investigate the predictive ability of the MRI-based vertebral bone quality (VBQ) score for pedicle screw loosening following instrumented transforaminal lumbar interbody fusion (TLIF). Methods: Data from patients who have received one or two-level instrumented TLIF from February 2014 to March 2015 were retrospectively collected. Pedicle screw loosening was diagnosed when the radiolucent zone around the screw exceeded 1 mm in plain radiographs. The T1-weighted MRI sagittal images were used for calculation of the VBQ score. The score was calculated with the median signal intensity value of L1 to L4 divided by the signal intensity value of cerebrospinal fluid at the L3 level. Univariate analysis and multivariate binary logistic regression analysis were performed. Receiver operating characteristic curve analysis assessed the predictive ability of the VBQ score on screw loosening. Results: Among the included 211 patients, 75 of them (35.55%) had pedicle screw loosening at the 24 month follow-up. Multivariable logistic regression analyses demonstrated that higher VBQ score (OR: 27.887 ± 0.514 ,95% CI: 10.189–76.326), male sex (female to male 0.323 ± 0.483, 0.126–0.833), and longer fusion length (2.578 ± 0.545, 1.166–5.701) were significant influencing factors for pedicle screw loosening. The VBQ score significantly predicted screw loosening with an accuracy of 78.9%. Conclusions: A higher VBQ score was an independent risk factor for pedicle screw loosening following instrumented TLIF. The MRI-based VBQ score showed good predictive ability for screw loosening and could be used as an alternative option for preoperative bone quality evaluation.